“Her talent was primarily male”. Art criticism and gender from the 1880s to the 1930s - Jaśkiewicz, Joanna (Ars inspiratio: Studies dedicated to Professor Eleonora Jedlińska, 2024)
Among the obstacles professional women artists faced in the late 19th and at the beginning of the 20th century, perhaps the most difficult to overcome were prejudices about the relationship between gender and creativity. Stereotypically, women were seen as incapable of artistic work, and any piece of art they created had to have a masculine element to be taken seriously. This way of thinking was echoed in many critical texts, even in those that were favorable in tone. This article collects a number of examples that allows one to trace how the gender of women artists affected the reception of their work.